Aviation Hazards Over the Jomsom Airport of Nepal as Revealed by Numerical Simulation of Local Flows - Regmi, Ram P. (Journal of Institute of Science and Technology, 2015)
Jomsom Airport of Nepal is considered to be one of the world’s most extreme airports. The frequency of aircraft crashing along the Kali Gandaki River Valley and over the Jomsom Airport is very high. Pre-monsoon time local flow characteristics over the Kali Gandaki Valley has been studied to understand the meteorological hazards for aviation activities along the valley and over the Jomsom Airport with the application of the WRF Modeling System initialized with NCEP meteorological, USGS 24 categories land use, and 30 second terrain data. Four days long simulation was carried out for the period of 15 May 0000 UTC to 19 May 0000 UTC, 2012 to capture the 16 May 2012 incidence of light aircraft crashing in the late morning time of the day. The study revealed that there are enough grounds to believe that the crashing of the plane resulted due to the adverse local flow system prevailing over the Jomsom Airport area during the period. The significant subsidence from the relatively strong boundary layer wind aloft, the ground level opposite wind and the low-level turbulence might have leaded the airplane to crash just after its takeoff from the runway. The local flow system over the Kali Gandaki Valley makes afternoon time flights over the Jomsom Airport almost impossible and the narrow slot of time during morning time is also not free from difficult situation. Journal of Institute of Science and Technology, 2014, 19(1): 111-120